DESIGN AND DEVELOPMENT OF TACTICAL MONITORING FORCE USING ONLINE BASED TELEMETRY SYSTEMS FOR MATAN BATALYON COMMANDO PASKHAS TEAM - Zainal Syahlan; Ahmadi Ahmadi; Suprayitno Suprayitno; Robert Radiyanto (JOURNAL ASRO, 2020)
The operational equipment of the Security and Rescue Team (Matan) of the Paskhas Command Battalion called the Integrated Personal Protection (IPP Set) is currently incomplete because monitoring of the implementation of the Matan Team's activities is limited to reports through radio / HT communication tools, so that in decision making actions by the Operations Commander Puskodalops is not optimal and accurate according to the conditions in the field. Therefore we need a system that can monitor the movements of the Matan Team that can monitor the position and visual forces in real time. This monitoring system using radio telemetry can transmit data in the form of GPS coordinates displayed by Google Map as well as visual image data recorded by FPV cameras in realtime using the 3DR telemetry transmission system 433 Mhz and VTX 5.8 Ghz mounted on a tactical helmet and received by ground station receiver antennas at Puskodalops, so that the position of the matan team personnel can be monitored and conditions in the field can be monitored in realtime so that the Operations Commander can make decisions more quickly, precisely and accurately according to field conditions.Keywords : Telemetry, Security and Rescue Team (Matan)